Managing Extension’s Internal Brand: Employees’ Perceptions of the Functions and Descriptors of Extension - Quisto Settle; Lauri M. Baker; Scott Stebner (Journal of Applied Communications, 2016)
Employees of UF/IFAS Extension were surveyed to determine their perceptions of the brand’s core identity. More specifically, they evaluated the importance of various functions the organization provides and the effectiveness of various terms for describing Extension work. Respondents included county faculty, county non-faculty, state faculty, and state non-faculty to gain perspectives of groups representing Extension’s brand in Florida. Results indicated employees perceived the core functions were providing research-based information, helping solve problems, providing training for clientele, and providing expertise. Education, training, and providing solutions were perceived to be the most effective terms for describing Extension work to the public. Given that these terms are viewed as most effective internally, these terms should also be used in external communications to provide consistency. “Extension” as a term was not viewed as particularly effective for representing to the public what Extension does. When comparing groups of Extension personnel, there were statistically significant differences, indicating Extension lacks a shared identity across the organization, which could be harmful. State-level faculty, in particular, had less positive viewpoints compared to other respondent groups. It was recommended that interactions be increased between state-level and county-level employees to help mitigate potential issues that would arise because of the organization being geographically distributed in the state and to help build shared identity. Future research was recommended to address the public’s views of functions and descriptors of Extension,
Keywords: Branding; Employees; Extension; Identity; Survey